One‐day postoperative intraocular pressure spikes after phacoemulsification cataract surgery in patients taking tamsulosin. Issue 12 (December 2016) - Bonnell, Levi N.; SooHoo, Jeffrey R.; Seibold, Leonard K.; Lynch, Anne M.; Wagner, Brandie D.; Davidson, Richard S.; Taravella, Michael J.
Abstract : Purpose : To evaluate the relationship between 1‐day postoperative intraocular pressure (IOP) after phacoemulsification cataract surgery and tamsulosin use. Setting : University of Colorado Health Eye Center, Aurora, Colorado, USA. Design : Retrospective cohort study. Methods : Registry data from men who had cataract surgery were used. Patients taking tamsulosin at the time of surgery were included as cases, while patients with no history of tamsulosin use were used as controls. The primary outcome was a 1‐day postoperative IOP spike defined as an IOP increase greater than 10 mm Hg compared with baseline or a 1‐day postoperative IOP of 30 mm Hg or higher. General estimating equations were used for analysis. Results : The study comprised 584 men (864 eyes). An IOP increase greater than 10 mm Hg or IOP 30 mm Hg or higher after cataract surgery occurred in 12.4% and 9.3%, respectively, of eyes in the tamsulosin group versus 4.4% and 2.1%, respectively, in the control group (all P = .001). After adjusting for significant covariates, patients on tamsulosin were 2.6 times (95% confidence interval [CI], 1.2‐5.7; P = .01] and 3.8 (95% CI, 1.3‐10.9; P = .01) more likely to have a 1‐day postoperative IOP increase greater than 10 mm Hg or a 1‐day postoperative IOP of 30 mm Hg or higher. Conclusion : Patients on tamsulosin had an increased risk of a 1‐day postoperative IOP spike after cataract surgery, showing the importance of identifying patients on tamsulosin preoperatively to better manage and potentially mitigate IOP spikes. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.